Gender-Based Biochemical Analysis of Serum Cholesterol, Triglycerides, and Fasting Blood Glucose in Adults from Derna, Libya - Elkhajkhaj, Marai; Naji Abdelsalam, (AlQalam Journal of Medical and Applied Sciences, 2025)
This study explores the biochemical relationship between serum triglycerides (TG), cholesterol (CHO), and fasting blood glucose (FBS) in adult males and females residing in Derna. A total of 52 participants (27 females and 25 males), aged 27–73 years, were recruited from the Derna Diabetes and Endocrinology Center. Blood samples were collected after 12 hours of fasting and analyzed using spectrophotometric techniques. The results revealed a strong positive correlation between TG and FBS (r = 0.52, p < 0.001), while CHO showed a moderate association with FBS (r = 0.41, p = 0.003). Gender-based differences were observed, with males exhibiting higher TG levels and females showing greater variability in glucose response. Age and acquired obesity were also linked to elevated biochemical markers, particularly in individuals over 50 years. Risk classification indicated that 40% of participants had high FBS levels and 30% had elevated TG, suggesting a substantial prevalence of metabolic risk. The findings support the use of TG as a predictive marker for glycemic dysregulation, especially in resource-limited settings. This study highlights the importance of early screening and gender-sensitive interventions to prevent diabetes and cardiovascular complications. It also emphasizes the need for regionally tailored public health strategies and further research into lipoprotein subtypes and their metabolic roles.